Declining temperature and increasing moisture sensitivity of shrub growth in the Low‐Arctic erect dwarf‐shrub tundra of western Greenland - Stef Weijers (Ecology and Evolution, 2022)
Abstract Evergreen dwarf shrubs respond swiftly to warming in the cool and dry High Arctic, but their response in the warmer Low Arctic, where they are expected to be outcompeted by taller species under future warming, remains to be clarified. Here, 12,528 annual growth increments, covering 122 years (1893–2014), were measured of 764 branches from 25 individuals of the evergreen dwarf shrub Cassiope tetragona from a Low‐Arctic erect dwarf‐shrub tundra site in western Greenland. In addition, branch initiation and mortality frequency time series were developed. The influence of seasonal climate and correspondence with fluctuations in regional normalized difference vegetation index (NDVI), a satellite‐proxy for vegetation productivity, were studied. Summer temperatures were the main driver of growth, while winter temperatures were the main non‐summer‐climate driver. During past and recent warm episodes, shrub growth diverged from summer temperatures. In recent decades, early summer precipitation has become the main growth‐limiting factor for some individuals, likely through micro‐topography‐determined soil moisture availability, and more than half of the shrubs studied became irresponsive to summer temperatures. There was correspondence between climatic drivers, C. tetragona growth and branch initiation frequency, and satellite‐observed vegetation productivity, suggesting the area's shrub‐dominated tundra vegetation is limited by similar climatic factors. Winter warming events were likely the predominant cause of branch mortality, while branching increased after years with poor growth and cooler‐than‐average summers. These findings show that the erect dwarf‐shrub tundra in the Low Arctic has already and will likely become decreasingly temperature‐ and increasingly moisture‐limited and that winter warming supports shrub growth, but increased extreme winter warming event frequency may increase branch mortality and vegetation damage. Such counter‐acting mechanisms could offer an explanation for the vegetation stability observed over large parts of the Arctic.